Myth and Immortality in Russian Folktales - Enrique Santos Marinas (Religions)
As Russian folklorist Vladimir Propp already set out in his monograph Theory and History of Folklore (1984), folktales, and in particular fairy tales, could preserve the remnants of myths and rites from very ancient stages of human civilisation, dating back to Prehistoric times themselves. The great Indoeuropeanist Georges Dumézil managed to confirm that the Slavic cultures are perhaps those which have best preserved the ancient rites to this day. As José Manuel Losada pointed out, the encounter with transcendence is one of the essential dimensions of myth that defines it and distinguishes it from other manifestations of human creativity. In this article, we will study the idea of immortality that can be found in Russian folktales as published by Aleksandr Afanasyev in his compilation (1855–1863) and trace back the remnants of the Indo-European religion and mythology that they can conceal.